Molecular epidemiology of Malaysian dengue 2 viruses isolated over twenty-five years (1968-1993) - Fong, M.Y.; Koh, C.L.; Lam, S.K. (1998)
The limited sequencing approach was used to study the molecular epidemiology of 24 Malaysian dengue 2 viruses which were isolated between 1968 and 1993. The sequences of a 240-nucleotide-long region across the envelope/non-structural 1 protein (E/NS1) gene junction of the isolates were determined and analysed. Alignment and comparison of the nucleotide and deduced amino acid sequences of the isolates revealed that nucleotide changes occurred mostly at the third position of a particular codon and were of the transition (A<->G, C<->U) type. Five nucleotide changes resulted in amino acid substitutions. Pairwise comparisons of the nucleotide sequences gave divergence values ranging from 9 to 9.2. At the amino acid level, the divergence ranged between 0 and 3.8. Based on the 6 divergence as the cut-off point for genotypic classification, the isolates were grouped into two genotypes, I and II. Comparison of the nucleotide sequences of the Malaysian dengue isolates with those of the dengue viruses of other regions of the world revealed that members of genotypes I and II were closely related to viruses from the Indian Ocean and Western Pacific regions, respectively.